Shade and Cd Conditions Strongly Impact the Physiological Responses of Purple Perilla - Zhang, Yiran; Zhang, Hanzhi (Frontiers in Environmental Science, 2022)
Plant metabolic regulation is an important strategy for dealing with abiotic stress, which can initiate dramatic changes in metabolite profiles. Metabolomic studies have been extensively used to reveal the responses of plants to abiotic stress, but research concerning how shade growth conditions impact the physiological responses of purple Perilla under Cd stress is still rare. In this study, we compared the metabolite profiles of purple Perilla exposed to shade and Cd stresses. The results showed that the metabolite profiles of purple Perilla under these stresses could be classified separately. Compared with the normal sunlight treatment, important energy metabolic pathways, including the citrate (TCA) cycle and glyoxylate and dicarboxylate metabolism, were inhibited under shade stress. Metabolite analysis revealed that pyruvate was involved in numerous metabolic pathways under Cd stress, and decreased pyruvate was regarded as a metabolite marker for physiological changes. The results show that increased thiamine is an important intermediate that is beneficial for enhancement of Cd stress tolerance.